Prototyping collaborative relationships between design and healthcare experts: mapping the patient journey. Issue 1 (2nd January 2017) - Reay, Stephen D.; Collier, Guy; Douglas, Reid; Hayes, Nick; Nakarada-Kordic, Ivana; Nair, Anil; Kennedy-Good, Justin
ABSTRACT: This case study presents the first project undertaken in a recent in-hospital design collaboration – the Design for Health and Wellbeing Lab (DHW Lab). Specifically, we explore some of the challenges and opportunities associated with designing a journey map for the Adult Emergency Department, the DHW Lab's first opportunity to put co-design into practice. The intention and outcome of this project was as much about designing a journey map prototype as it was about building the interdisciplinary relationships that would help enable future successful design-led collaborations. As such, the notion of prototyping was applied to both generate artefacts to communicate care pathways to patients and families, as well as a way to build and test collaborative relationships between designers and clinical staff. The outcomes of the project resulted in new products to help patients and families negotiate a complex emergency department as well as gaining insight into how to bring people from different backgrounds together to start a design-led conversation around a culture of care within a hospital.